2002
DOI: 10.1038/sj.jim.7000237
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature on the aerobic stability of wheat and corn silages

Abstract: The aim of this work was to study the effects of temperature on the aerobic stability of wheat and corn silages. Three silage samples from each crop were taken from the faces of six different commercial bunker silos immediately after unloading them. The samples were exposed to air for 3 or 6 days at 10, 20, 30 or 40 degrees C. The most intensive deterioration occurred at 30 degrees C. Samples incubated at 30 degrees C had the highest yeast counts, most prolific CO(2) production and greatest increases in pH. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
2
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 0 publications
3
63
2
9
Order By: Relevance
“…When the silo is opened, the anaerobic environment is changed to an aerobic one and microorganisms which remain dormant in the absence of air multiply, resulting in a deterioration of silages, especially in warm climates (Woolford, 1990; Ashbell et al, 2002). Many workers have found that aerobic deterioration resulted from the activity of aerobic bacteria, yeast and mold utilizing residue WSC and lactic acid producing a rising pH and energy loss and even the possibility of producing harmful by products (Honig et al, 1980; MuDonald et al, 1991; Weinberg et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…When the silo is opened, the anaerobic environment is changed to an aerobic one and microorganisms which remain dormant in the absence of air multiply, resulting in a deterioration of silages, especially in warm climates (Woolford, 1990; Ashbell et al, 2002). Many workers have found that aerobic deterioration resulted from the activity of aerobic bacteria, yeast and mold utilizing residue WSC and lactic acid producing a rising pH and energy loss and even the possibility of producing harmful by products (Honig et al, 1980; MuDonald et al, 1991; Weinberg et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…High temperatures during ensiling adversely affect silage fermentation and aerobic stability (Garcia et al 1989;Ashbell et al 2002). Garcia et al (1989) reported that high ensiling temperature decreased production of organic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Corn (Zea mays) silage is sensitive to aerobic deterioration losses (Weinberg et al 2011) as well-fermented silages and those with high nutritional value have a higher substrate availability for spoilage microorganisms (Cai et al 1999) and produce lower content of substances that inhibit such microorganisms (O'Kiely and Muck 1992). In hot-climate environments, high temperatures during ensiling, storage and unloading phases may increase the rate of growth of such microorganisms, leading to an intensified deterioration process (Ashbell et al 2002). Aerobic deterioration of silage is considered undesirable because it promotes the loss of dry matter (DM), reduces nutritional value, and affects intake and animal performance (Gerlach et al 2013).…”
Section: Introductionmentioning
confidence: 99%